Automatic Detection of Focal Cortical Dysplasia Type II in MRI: Is the Application of Surface-Based Morphometry and Machine Learning Promising? - Ganji, Zohreh; Hakak, Mohsen Aghaee; Zamanpour, Seyed Amir; Zare, Hoda (Frontiers in Human Neuroscience, 2021)
Background and objectives: Focal cortical dysplasia is a type of the malformations of cortical development (MCD) and one of the leading causes of drug-resistant epilepsy. Postoperative results improve the diagnosis of lesions on structural MRIs. Advances in quantitative algorithms have increased the identification of focal cortical dysplasia lesions. However, due to the significant differences in size, shape, and location of the lesion in different patients and a big deal of time for objective diagnosis of lesion as well as the dependence of the individual interpretation, sensitive approaches are required to address the challenge of lesion diagnosis. In this research, an FCD computer-aided diagnostic system to improve existing methods is presented. Methods: MRI data were collected from 58 participants (30 with histologically confirmed FCD type II and 28 without a record of any neurological prognosis). Morphological and intensity-based features were calculated for each cortical surface and inserted into an artificial neural network. Statistical examinations evaluated classifier efficiency. Results: Neural network evaluation metrics, sensitivity, specificity, and accuracy were 96.7%, 100%, and 98.6%, respectively. Furthermore, the accuracy of classifier for the detection of lobe and hemisphere of the brain, where the FCD lesion is located was 84.2% and 77.3%, respectively. Conclusion: Analyzing surface-based features by automated machine learning can give a quantitative and objective diagnosis of FCD lesions in the pre-surgical assessment and improve post-surgical outcomes.